COMMUNICATIVE EFFECTS OF METAPHOR IN MEDICAL DISCOURSE: A COVID-19 PARADIGM - Iyanda Kugbayi , Lateef (International Journal of Arts, Languages, Linguistics and Literary Studies, 2023)
The goal of every human conversation, to a great extent, is meaning making achievement. Hence, the listener’s ability to cognitively process the choices the speaker makes in connection with the physical reality is a major factor for the achievement of a meaningful interpretation of discourse. That emphasises the significance of metaphor to the production and meaningful interpretation of discourse. Considering the assertion from the point of view of the COVID-19 upsurge, one could note plethora instances that attracted productions of medical discourses for populations within and beyond the borderline of medical science. Incidentally, a great deal of metaphors are woven into those discourses and the addressed, regardless of their world experience, are faced with the challenge of reasoning out the ways by which the metaphors have been structured in the discourses to achieve meaningful interpretations and identification of speakers’ intentions. Against the backdrop, this paper purposively selects and analyses excerpts from discourses of health professionals like the Director General of the World Health Organisation, and some country ministers of health on COVID-19 to foreground the communicative effects of metaphors in the selected medical discourses, using the “Conceptual Metaphor Theory” of Fauconnier and Turner (1998) as a theoretical framework. The paper establishes that metaphors influence meaningful interpretation of medical discourses on COVID-19 by revealing the duality effects of the choice’s health practitioners make in their speeches and cognitive needs to decipher the indirect goal of the choices from their direct forms. It therefore concludes that health practitioners’ audiences need to expand their cognitive capacities to work out the specific meanings of the choices that are made in the description of COVID-19 related issues.